THE EFFECT OF IMPLEMENTING E-ASSESSMENT ON PERFORMANCE AND WORK MOTIVATION EMPLOYEE DURING THE CO-19 PANDEMIC (CASE STUDY) PRINGSEWU REGENCY GOVERNMENT OFFICE - Winia Waziana; Ricco Herdiyan Saputra; M Ridho Magribi; Dita Novitasari (IJISCS (International Journal of Information System and Computer Science), 2022)
The Pringsewu Regency Government is currently actively motivating its employees to always improve their performance by implementing an E-performance application system as a measuring tool for employee competence. Based on Law no. 5 of 2014 concerning the State Civil Apparatus, concerning the performance of civil servants which aims to ensure the objectivity of fostering civil servants based on the achievement system and career system. During the Co-19 pandemic, employees are expected to continue to carry out their duties optimally. Therefore, the author examines the effect of implementing E-Assessment on employee work motivation during the COVID-19 pandemic at the Pringsewu Regency Government office. This study uses a qualitative descriptive research method with an inductive approach. The method of data collection is through interviews, observation, and documentation. The author analyzes the data, starting with data collection, data reduction, data presentation, and generating conclusions or validation, following the steps used to analyze the problem and obtain results. The result of implementing E-Assessment on employee work motivation at the Pringsewu Regency Government Office is an increase in employee performance during the pandemic. Employees are motivated to complete their tasks optimally despite the pandemic. Several supporting factors that can motivate employees are 1). Adequate human resources, financial resources, and equipment. 2). Characteristics of implementing organizations. 3). Smooth communication between organizations.